2017
DOI: 10.1017/s0007114517001593
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to the Mediterranean diet is associated with the gut microbiota pattern and gastrointestinal characteristics in an adult population

Abstract: This study aimed to explore the potential associations of adherence to the Mediterranean diet with gut microbiota characteristics and gastrointestinal symptomatology in an adult population. Other long-term dietary habits (e.g. consumption of snacks and junk food or stimulant intake) were also evaluated in terms of the gut microbiota profile. Participants (n 120) underwent anthropometric, dietary, physical activity and lifestyle evaluation. Adherence to the Mediterranean diet was assessed using a Mediterranean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
176
1
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 240 publications
(194 citation statements)
references
References 59 publications
(103 reference statements)
8
176
1
9
Order By: Relevance
“…), which have been shown to exert antioxidant and antiinflammatory effects and thereby may conceivably protect from neurodegeneration. 36,[41][42][43][44] Concomitantly, these MeDi components and the whole MeDi pattern have been associated with favorable gut microbiota characteristics, [45][46][47] possibly ameliorating the gut-tobrain signaling and therefore beneficially affecting neuronal functioning in both the enteral and central nervous system. [38][39][40]48 Nevertheless, given that the association of MeDi with lower probability score of pPD in our study still remains when performing the analysis without constipation, this raises the possibility that association of MeDi with other pPD markers may be also pertinent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…), which have been shown to exert antioxidant and antiinflammatory effects and thereby may conceivably protect from neurodegeneration. 36,[41][42][43][44] Concomitantly, these MeDi components and the whole MeDi pattern have been associated with favorable gut microbiota characteristics, [45][46][47] possibly ameliorating the gut-tobrain signaling and therefore beneficially affecting neuronal functioning in both the enteral and central nervous system. [38][39][40]48 Nevertheless, given that the association of MeDi with lower probability score of pPD in our study still remains when performing the analysis without constipation, this raises the possibility that association of MeDi with other pPD markers may be also pertinent.…”
Section: Discussionmentioning
confidence: 99%
“…In such a case, adherence to the MeDi may have masked early features of pPD. Phrased differently, MeDi adherence may be influencing the probability of individual aspects of the PD risk/prodromal phenotype (see above, 46,50,52 ) but without being necessarily associated with the underlying biological mechanisms. MeDi may also have a role in modulating pathways that are related to the aging process in general, such as brain atrophy [53][54][55] and telomere length.…”
Section: Discussionmentioning
confidence: 99%
“…A raft of previous studies has revealed that this eating pattern could positively affect gut microbial communities. Mitsiu et al [115] described that individuals with higher Mediterranean diet scores had lower Escherichia coli counts, a higher Bifidobacteria to E. coli ratio, increased levels and prevalence of Candida albicans, and a higher molar ratio of acetate compared with subjects with low adherence. De Filippis et al [116] reported that high-level consumption of plant foodstuffs consistent with an MD was associated with a beneficial microbiome-related metabolomic profile (higher Prevotella and certain fiber-degrading Firmicutes profiles, higher SCFAs production) in subjects ostensibly consuming a Western diet [116].…”
Section: Mediterranean Diet (Md) and Gut Microbiotamentioning
confidence: 99%
“…Studies linking increased abundance of E. coli have shown that higher consumption of snack and junk food products results in an increase of E. coli counts and suppression of beneficial lactobacilli and butyrate-producing Firmicutes members (eg., F. prausnitzii). These changes represent a potential detrimental inflammatory gut microbiota milieu for the host [9]. In contrast, a long-term polysaccharide-rich diet (high in fiber and resistant starch) has been linked to lower abundance of members of the Enterobacteriaceae taxa (Shigella and Escherichia).…”
Section: The Mycobiome Diet Rebalances the Bacterial Community In Thementioning
confidence: 99%
“…Also, it borrows from the Paleo-style diet's whole natural food philosophy, but does not avoid fiber-rich and nutrient-dense legumes, which provide an excellent source of food (specifically fiber and resistant starch) for the beneficial members of the microbiome. The mycobiome diet furthermore avoids the mediterranean diet ' s overuse of complex carbohydrates and grains, which increase the prevalence and abundance of harmful fungi, as well as its penchant for alcohol, which has been proven to decrease microbial diversity [9].…”
Section: Introductionmentioning
confidence: 99%